Determinants of Mobilization Speed Among Post-Caesarean Mothers in Sidoarjo - Sri Mukhodhim Faridah Hanum; Hesty Widowati; Fita (Universitas Muhammadiyah Sidoarjo, 2026)
A Caesarean section (CS) is a surgical procedure that delivers a fetus through an incision in the abdominal wall and uterus . Important aspects to consider include surgical wound care, meeting the mother's fluid and nutritional needs, pain management, and early mobilization. In postpartum cesarean section patients who do not undergo early mobilization, possible effects include increased body temperature, abnormal bleeding, thrombosis, poor involution, obstructed blood flow, and increased pain intensity. This study aims to identify the characteristics and speed of maternal mobilization after cesarean section at Rahman Rahim Hospital, Sidoarjo. This study used an analytical observational design with a cross-sectional approach. The study sample consisted of 60 respondents. The independent variables were maternal characteristics, including age, occupation, and pain intensity, while the dependent variable was the speed of mobilization in post- cesarean section mothers. The results of the Chi-square test showed that maternal age and occupation were not significantly related to the speed of mobilization. However, pain intensity had a significant relationship with the speed of mobilization, with a p-value of 0.000, indicating a statistically significant relationship between pain intensity and the speed of maternal mobilization after a cesarean section.